2022
DOI: 10.1371/journal.pone.0274143
|View full text |Cite
|
Sign up to set email alerts
|

Dogs can discriminate between human baseline and psychological stress condition odours

Abstract: Previous research suggests that dogs can detect when humans are experiencing stress. This study tested whether baseline and stress odours were distinguishable to dogs, using a double-blind, two-phase, three-alternative forced-choice procedure. Combined breath and sweat samples were obtained from participants at baseline, and after a stress-inducing (mental arithmetic) task. Participants’ stress was validated with self-report and physiological measures recorded via a Biopac MP150 system. Thirty-six participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The strong positive correlation between Ivy's performance and the donors' State Anxiety indicates her sensitivity primarily to the SAM axis volatiles. This is consistent with a prior study ( 53 ) which provided evidence of canines' ability to detect human stress volatiles released in mere three minutes (most likely from SAM, not HPA axis). In contrast, Callie may have responded to glucocorticoid-related VOC's (e.g., from cortisol release in the HPA axis).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The strong positive correlation between Ivy's performance and the donors' State Anxiety indicates her sensitivity primarily to the SAM axis volatiles. This is consistent with a prior study ( 53 ) which provided evidence of canines' ability to detect human stress volatiles released in mere three minutes (most likely from SAM, not HPA axis). In contrast, Callie may have responded to glucocorticoid-related VOC's (e.g., from cortisol release in the HPA axis).…”
Section: Discussionsupporting
confidence: 91%
“…Forty pet dogs displayed more stress-related behaviours and arousal (e.g., elevated heart rate) when sniffing pooled samples from the fear vs. joy or control (no human odour) conditions ( 52 ). A third study ( 53 ) collected breath and sweat samples from 36 humans immediately before and after a mental arithmetic task and validated their stress by blood pressure, heart rate, and self-report. The validated samples were then presented to four formerly-trained scent-detection dogs in a three alternative forced choice discrimination task (baseline and stress samples of the same donor, and a blank sample).…”
Section: Background Informationmentioning
confidence: 99%
“…When in use, each specimen jar (without lid) containing devil faeces was placed in a separate metal scent pot with a mesh lid to allow dogs to sniff, but not access the source of, the scent. To avoid saliva contamination that could influence the dog’s choice during training, scent pots were sanitised between each dog using 70% isopropanol wipes and allowed to dry before use ( 44 , 45 ), and 2–5 used scent pots were also randomly replaced with clean, unused pots. During assessments, however, clean scent pots were used for each dog.…”
Section: Methodsmentioning
confidence: 99%
“…During assessments, however, clean scent pots were used for each dog. After each training/assessment day, scent pots were washed in a designated dishwasher (with no detergent) to remove organic material, air-dried, and then sprayed with 70% isopropanol and left to dry ( 44 , 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have suggested that domestic mammals can perceive our emotions through olfaction and are influenced by them. For example, cattle sniffed human sweat produced in a non-stressful context for longer than that produced in a stressful context 29 , and dogs can distinguish between human odors from baseline and psychological stress conditions 30 . Dogs also showed more stress-like behaviors 25 and interacted less with an unfamiliar human 31 , 32 after sniffing human sweat collected while watching a fear-inducing video rather than a joy-inducing video.…”
Section: Introductionmentioning
confidence: 99%